This lie will kill you / Chelsea Pitcher. - Pitcher, Chelsea (Simon & Schuster, 2018)
One year ago, there was a party. At the party, someone died. Five teens each played a part and, up until now, no one has told the truth. But tonight, the five survivors arrive at an isolated mansion in the hills, expecting to compete in a contest with a $50,000 grand prize. Of course, some things are too good to be true. They were each so desperate for the prize, they didn't question the odd, rather exclusive invitation until it was too late. Now, they realise they've been lured together by a person bent on revenge, a person who will stop at nothing to uncover what actually happened.